Análisis, diseño e implementación de un sistema web de ayuda y evaluación docente utilizando la metodología Ágil de desarrollo de software Crystal Clear y el Framework de programación Django para el Colegio Nacional Técnico Kleber Franco Cruz. - Lima Sigüenza, Darwin Antonio (2014)
The College Kléber Franco Cruz city of Machala, had several problems and disadvantages regarding the teaching by teachers to students educativo.Uno campus of the main problems was that teachers lacked a tool academic computing that would share resources with students quick and easy way to save time and effort.